Technology Trends in Translation: A Comparative Analysis of Machine and Human Translation - Waty Kembaren, Farida Repelita; Hasibuan, Ardina Khoirunnisa; Natasya, Azzahra (Institut Agama Islam Sunan Giri Ponorogo, 2023)
The development of translation technology, whether through machines or humans, has created a new paradigm in cross-language information exchange. This research aims to carry out a comparative analysis between translation results produced by machine translation systems and human translations. The method used in this research is qualitative in a comprehensive literature review aimed at understanding the latest developments in translation technology, with a particular focus on comparing machine and human translation. The data collection technique is through a literature review system from the study of scientific articles and data analysis using a qualitative approach. The results show that comparisons between machine and human translation involve careful assessment of each method's accuracy, consistency, and flexibility. While machine translation excels in speed and consistency, human translation provides advantages in terms of depth of accuracy and greater flexibility. The results of this research will provide a valuable contribution to further understanding of the role of technology in the translation industry and its implications for the use of translation in various communication contexts.